Galactic Cosmic Ray Origins and OB Associations: Evidence from SuperTIGER Observations of Elements _(26)Fe through _(40)Zr - Murphy, R. P.; Sasaki, M.; Binns, W. R.; Brandt, T. J.; Hams, T.; Israel, M. H.; Labrador, A. W.; Link, J. T.; Mewaldt, R. A.; Mitchell, J. W.; Rauch, B. F.; Sakai, K.; et al. (The Astrophysical Journal, 2016)
We report abundances of elements from _(26)Fe to _(40)Zr in the cosmic radiation measured by the SuperTIGER (Trans-Iron Galactic Element Recorder) instrument during 55 days of exposure on a long-duration balloon flight over Antarctica. These observations resolve elemental abundances in this charge range with single-element resolution and good statistics. These results support a model of cosmic ray origin in which the source material consists of a mixture of 19_(-6^(+11)% material from massive stars and ~81% normal interstellar medium material with solar system abundances. The results also show a preferential acceleration of refractory elements (found in interstellar dust grains) by a factor of ~4 over volatile elements (found in interstellar gas) ordered by atomic mass (A). Both the refractory and volatile elements show a mass-dependent enhancement with similar slopes. Â© 2016 American Astronomical Society. Received 2016 August 2; revised 2016 August 18; accepted 2016 August 21; published 2016 November 3. We gratefully acknowledge the excellent and highly professional work of the NASA Columbia Scientific Balloon Facility, the NASA Balloon Program Office, and the NSF Office of Polar Programs, who together made possible the record long-duration balloon flight of SuperTIGER. NASA supported this research under the ROSES 2007 APRA program under grants NNX09AC17G to Washington University in St. Louis and NNX09AC18G to the California Institute of Technology and the Jet Propulsion Laboratory, and APRA07-0146 to NASA/GSFC. We thank Nasser Barghouty for his help calculating interaction cross sections for the Galactic propagation. We are also grateful for support from the Peggy and Steve Fossett Foundation and the McDonnell Center for the Space Sciences at Washington University. We thank the referee who identified himself as Don Ellison for his helpful comments that improved this paper. Published - Murphy_2016_ApJ_831_148.pdf Submitted - 1608.08183v1.pdf